Прясельця пізнього Трипілля — Троя(нів) та Троя - Бурдо, Н.Б. (Археологія, 2018)
Керамічні прясельця кружала належать до категорії артефактів, що була значно поширеною на етапі Трипілля
СІІ, проте досі залишається слабо вивченою. У роботі
пропонується систематизація та класифікація цієї категорії знахідок пізнього етапу Трипілля, їх контекстний
та функціональний аналіз, порівняльний аналіз трипільських прясел із прясельцями кружалами археологічних
культур доби ранньої бронзи Балкано-Карпатського регіону. Трипольские керамические пряслица — плохо изученная категория артефактов. Этот вид изделий широко распространен и характерен для поздней стадии Триполья (C II). На поселении Троянов было обнаружено более 200 пряслиц. Десятки этих предметов были получены во время раскопок таких поселений, как Паволоч, Городск и др.
Большинство находок пряслиц происходит из руин сожженных жилищ. На многих поселениях позднего Триполья изделия найдены в культовых ямах. Находки этих предметов также хорошо известны в культурном слое
Касперовци пещеры Вертебы, признанной святилищем. Кроме того, пряслица были частью погребального инвентаря в некрополе Выхватинцы. В Колодистом они были обнаружены в могилах, размещенных под курганом, в
горшках, заполненных кальцинированными человеческими костями. В другом случае пряслице было помещено
в пепел в некрополях Софиевской группы.
Формальный анализ пряслиц показывает разнообразие типов, которые не образуют никаких групп. Форма,
размеры и вес не влияли на их технологические свойства. Значительное число пряслиц украшено углубленным
декором, а некоторые орнаментальные узоры являются общими для всех локально-хронологических групп Триполья CII.
Внешний вид пряслиц, контекст их находки и символическое украшение позволяют рассматривать их как
религиозные объекты. Их декор технологически не связан с производством. Традиция использования пряслиц
в Tриполье CII возникает наряду с феноменом «баденизации» этой культуры в начале раннего бронзового века.
Общие черты элементов Tриполья CII и находки из слоев раннего бронзового века Трои вынуждает искать ответы
на вопрос о распространении сакральных традиций в Старом Свете. Trypillian ceramic spindle whorls are a poorly understood category of artifacts. They do not even always fall into the general
reviews of Trypillian materials. This type of items is widespread and is typical for the late stage of Trypillia (CII). More than
200 spindle whorls were found in the Troianiv settlement. Dozens of these items were obtained during the excavation of such
settlements, as Pavoloch, Horodsk and others.
Contextual analysis of the spindle whorls finds shows that most of them originated from the ruins of burnt dwellings. In
many late Trypillian settlements, they are found in pits, which can be interpreted as religious objects. Finds of these items are
also well known in the Kasperivtsi cultural layer of the Verteba cave, recognized as a sanctuary. In addition, spindle whorls
were part of the funeral gifts in the Vykhvatyntsi necropolis. In Kolodyste they were discovered in graves placed under the
barrow. Here they were located in pots, full of calcinated human bones. In other case a spindle whorl was placed in ashes at
the necropolises of Sofiivka group.
Formal analysis of spindle whorls shows the diversity of their types, which do not form any groups. The shape,
measurements and weight did not affect their technological properties. A significant amount of them is decorated with a
deepened decor, and certain ornamental patterns are common to all the locally-chronological groups of Trypillia C II.
The exterior view of spindle whorls, the context of their finding and the symbolic decoration makes it possible to
consider them as religious objects. Their decoration isn’t connected technologically with their manufacturing. The tradition
of spindle whorls usage in Trypillia C II arises along with the phenomenon of “badenization” of this culture at the beginning
of the Early Bronze Age (EBA). The common features of Trypillia C II items and finds from the Troy’s EBA layers allows
seeking answers to the question of the spread of sacral traditions in the Old World.